2021
DOI: 10.47176/mjiri.35.156
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Platelet-Rich Plasma as an Adjuvant Therapy to Endoscopic Sinus Surgery in Anosmia Patients with Sinonasal Polyposis: A Randomized Controlled Clinical Trial

Abstract: Olfactory dysfunction in patients with sinonasal polyposis is a major therapeutic challenge. However, intranasal glucocorticoids are widely accepted for the management of patients with anosmia, antihistamines, systemic glucocorticoids, and antibiotics are indicated in special cases. Besides, surgical intervention is an effective choice in patients in whom conservative treatments have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In this single‐blinded, randomized controlled study, PRP treatment resulted in a greater improvement in overall olfaction scores compared with placebo with a 12.5 times greater likelihood in achieving a treatment response at 3 months. Submucosal injections of PRP into the olfactory cleft were well tolerated without significant adverse effects and did not worsen smell function, as previously noted in our pilot study and other studies utilizing intranasal PRP 20–22,28,29 . These data suggest that PRP has the potential as a safe treatment option for patients with COVID‐19 smell loss.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this single‐blinded, randomized controlled study, PRP treatment resulted in a greater improvement in overall olfaction scores compared with placebo with a 12.5 times greater likelihood in achieving a treatment response at 3 months. Submucosal injections of PRP into the olfactory cleft were well tolerated without significant adverse effects and did not worsen smell function, as previously noted in our pilot study and other studies utilizing intranasal PRP 20–22,28,29 . These data suggest that PRP has the potential as a safe treatment option for patients with COVID‐19 smell loss.…”
Section: Discussionsupporting
confidence: 84%
“…Submucosal injections of PRP into the olfactory cleft were well tolerated without significant adverse effects and did not worsen smell function, as previously noted in our pilot study and other studies utilizing intranasal PRP. 20 , 21 , 22 , 28 , 29 These data suggest that PRP has the potential as a safe treatment option for patients with COVID‐19 smell loss.…”
Section: Discussionmentioning
confidence: 89%
“…24,25 To date, the injection of PRP into the olfactory clefts of patients with OD was attempted in a few small-cohort studies and reported safety 13 and promising findings. 12,[26][27][28] The primary finding of our study may suggest better significant improvements in both patient-reported outcome olfactory questionnaire and psychophysical evaluations in PRP patients compared with controls. In addition to the potential effectiveness of PRP in COVID-19 patients with OD, our preliminary 13 and current data supported that this procedure is safe and not associated with adverse events.…”
Section: Discussionmentioning
confidence: 68%
“…Precisely, in Otolaryngology–Head and Neck Surgery, PRP may be indicated in the management of vocal fold lesions, 22 neck fistula, 23 or tympanic membrane perforation 24,25 . To date, the injection of PRP into the olfactory clefts of patients with OD was attempted in a few small‐cohort studies and reported safety 13 and promising findings 12,26‐28 …”
Section: Discussionmentioning
confidence: 99%
“…At the 3-month follow-up, five patients with hyposmia exhibited improvement, with 60% achieving normosmia. Forty-eight anosmia patients with sinonasal polyposis participated in randomized controlled research by Goljanian Tabrizi et al [ 38 ] to evaluate the effectiveness of platelet-rich plasma as an adjuvant therapy to endoscopic sinus surgery. Their research found that PRP injection had no immediate impact on patients with sinonasal polyposis’ ability to regain their olfactory function.…”
Section: Discussionmentioning
confidence: 99%